Creme Sugar: Business Plan / Fadha Nur Azhar ... [et al.] - Azhar, Fadha Nur; Mohamad Saufi, Nurfarhah; Mohd Ridzuan, Nur Ain Danishah; Razizad, Raza Syaqireen (2021)
The prospects of the business is to build more branch all across Malaysia.